GENOTYPE FERTILIZER DOSES INTERACTION FOR HYBRID SEED YIELD OF RICE (Oryza sativa L.) (Bangladesh Journal of Plant Breeding and Genetics, 2011)
The experiment was laid out in a Randomized Completely Block Design (RCBD) during the Boro season (2006-2007) at Bangabandhu Sheikh Mujibur Rahaman Agricultural University-Gazipur; Bangladesh Agricultural University-Mymensingh and Bangladesh Rural Development Academy, Bogra. Among the three introduced CMS lines, CMS-2 was highly responsive to environment (fertilizer dose) for yield due to the highest mean, considerable phenotypic index, regression coefficient greater than unity (bi > 1) and insignificant deviation from regression (S2di ? 0). CMS line CMS-1 showed regression coefficient near unity (bi ?1) and significant deviation from regression (S2di > 0) indicating stability for yield but its stability is unpredictable due to significant deviation from regression. CMS line Alok showed significant regression coefficient (bi >1) indicating highly responsive to fertilizer doses but significant deviation from regression made it unpredictable linear prediction. These results also explain that the production based on regression analysis for the genotypes differed considerably in respect to stability performances.DOI: http://dx.doi.org/10.3329/bjpbg.v24i1.16998